Hubungan Antara Intensitas Penggunaan Aplikasi Tiktok dengan Psychological Well Being pada Gen-Z - Jovita Sasha Sani; Fatchiah Kertamuda (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
With the rapid advancement of technology, social media platforms like TikTok have become significantly integrated into the daily lives of Generation Z. This study aims to explore the connection between the intensity of TikTok use and the psychological well-being of Gen-Z individuals. The research employs a quantitative design, analyzing data through Pearson's product-moment correlation test and simple regression analysis using SPSS version 26. A total of 161 respondents were selected via convenience sampling. The instruments used include a TikTok usage intensity scale developed by Izzatur Rayyan (2024) and Ryff’s 18-item Scales of Psychological Well-Being (Ryff et al., 2010). The findings indicate no significant relationship between TikTok usage intensity and psychological well-being, as evidenced by a significance value (Sig.) of 0.548 (p>0.05) between the TikTok intensity variable and psychological well-being.